2017
DOI: 10.1073/pnas.1613237114
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal CX26 removal impairs neocortical development and leads to elevated anxiety

Abstract: Electrical coupling between excitatory neurons in the neocortex is developmentally regulated. It is initially prominent but eliminated at later developmental stages when chemical synapses emerge. However, it remains largely unclear whether early electrical coupling networks broadly contribute to neocortical circuit formation and animal behavior. Here, we report that neonatal electrical coupling between neocortical excitatory neurons is critical for proper neuronal development, synapse formation, and animal beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 36 publications
1
12
1
Order By: Relevance
“…Cx43, Cx40 and Cx45 play the major role in the gap junction coupling capabilities of MSCs ( Bodi et al, 2004 ; Valiunas et al, 2004 ). We expected that the differentiation of MSCs into neuron-like cells would down-regulate mesenchymal connexins like Cx43, Cx40 and Cx37 while up-regulating neuronal connexins like Cx26, Cx45 and especially Cx36 ( Rozental et al, 2000 ; Söhl et al, 2005 ; Eugenin et al, 2012 ; Su et al, 2017 ). Our analysis of connexin expression in the transdifferentiated neuron-like cells showed a significant down-regulation of the mesenchymal connexins Cx43, Cx40 and Cx37 and an upregulation of Cx26, thereby confirming our expectations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cx43, Cx40 and Cx45 play the major role in the gap junction coupling capabilities of MSCs ( Bodi et al, 2004 ; Valiunas et al, 2004 ). We expected that the differentiation of MSCs into neuron-like cells would down-regulate mesenchymal connexins like Cx43, Cx40 and Cx37 while up-regulating neuronal connexins like Cx26, Cx45 and especially Cx36 ( Rozental et al, 2000 ; Söhl et al, 2005 ; Eugenin et al, 2012 ; Su et al, 2017 ). Our analysis of connexin expression in the transdifferentiated neuron-like cells showed a significant down-regulation of the mesenchymal connexins Cx43, Cx40 and Cx37 and an upregulation of Cx26, thereby confirming our expectations.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs are extensively gap junction-coupled and mainly express Cx43, as well as Cx40 and Cx45 ( Dorshkind et al, 1993 ; Bodi et al, 2004 ; Valiunas et al, 2004 ). Neurons are also coupled by gap junctions ( Lo Turco and Kriegstein, 1991 ; Bittman et al, 1997 ) which are mainly composed of the connexins Cx26, Cx30.2, Cx45 and particularly Cx36 ( Leung et al, 2002 ; Kreuzberg et al, 2008 ; Eugenin et al, 2012 ; Su et al, 2017 ). Amongst these, Cx36 is the most prominent neuronal connexin in adult electrical synapses and plays important roles in the developing brain ( Belluardo et al, 2000 ; Condorelli et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…Vertebrate gap junction channels are composed of proteins called connexins. In neurons, connexin 36 is the predominant gap-junctional protein (Connors and Long, 2004), although other connexins are present as well: for example, Cx45 was found in retinal neurons (Li et al, 2008), and Cx26 occurs in neonatal excitatory cells of the neocortex (Su et al, 2017).…”
Section: Spikelets Resulting From Electrotonic Coupling By Gap Junctionsmentioning
confidence: 99%
“…Yu et al (2012) reported that sister pyramidal neurons are most likely to be coupled during development and that such coupling in turn regulates specific local chemical synaptic excitatory circuits, which may also occur in a similar sequence during the development of other brain and spinal cord regions. Su et al (2017) found that Cx26 occurs in superficial layers of the cortex and is important for the development not only of synaptic connections but also of dendrites and for the ability of the more mature cortex to produce network oscillations. However, immunofluorescence labeling of Cx26 is not detectable in mature cortex, and its expression in adult brain appears to be restricted to a minor subpopulation of astrocytes (Nagy et al, 2001(Nagy et al, , 2011.…”
Section: Gap Junctions In Developing and Adult Neocortexmentioning
confidence: 99%